The Effect of Financial Leverage on Profitability in the Food and Beverage Industry (2017-2021) - Moridu, Irwan (Penelitian dan Pengembangan Ilmu, 2024)
This study aims to investigate the effect of financial leverage, that's measured through the Debt to Asset Ratio (DAR) and Debt to equity Ratio (DER), on return on assets (ROA) in food and beverage sector companies indexed at the Indonesia stock change (BEI). at some stage in the 2017-2021 period. Financial report records from 14 corporations selected the usage of the purposive sampling technique was analyzed via a couple of linear regression. The studies results show that the DAR ratio does not have an extensive effect on ROA, while the DER ratio has a giant high quality that has an effect on ROA. This research presents critical perception into capital structure management and its effect on organisation financial performance amidst the dynamics of the food and beverage industry.